Pain Anticipation and Nocebo-Related Responses: A Descriptive Mini-Review of Functional Neuroimaging Studies in Normal Subjects and Precious Hints on Pain Processing in the Context of Neurodegenerative Disorders - Amanzio, Martina; Palermo, Sara (Frontiers in Pharmacology, 2019)
The exacerbating of a clinical condition or the occurrence of negative symptoms after an inert substance dispensation or a sham treatment is known as “nocebo effect”. Nocebo is the psychobiological effect due to the negative psychosocial context that accompanies a therapy and it is a direct consequence of negative expectations by the patients and their own personal characteristics. Although the clinical relevance of the phenomenon is now recognised, a small number of studies has tried to ascertain its neural underpinnings (that it means nocebo responses). Moreover, there is no consensus on the brain networks involved in nocebo processes in humans. In particular, nocebo hyperalgesia has attracted almost no research attention. We conducted a mini-review on the few experimental pain fMRI studies of nocebo responses to discuss how negative expectancies and conditioning effects engage brain networks to modulate pain experiences. Moreover, we present possible clinical implications considering Alzheimer’s disease and behavioural frontotemporal dementia, in which the existence of a hypothetically disrupted neurocognitive anticipatory network – secondary to an endogenous pain modulatory system damage - may be responsable of pain processing alterations.